USO DA RADIAÇÃO ULTRAVIOLETA PARA DESINFECÇÃO DE EFLUENTE DE REATOR ANAERÓBIO - PEDROSO, CARLOS RAPHAEL (2015)
The purpose of the involved research was to evaluate the applicability of the UV radiation in the disinfection process of the up-flow anaerobic sludge blanket reactor (UASB) followed by anaerobic filter. We employed an UV reactor in countertop levels working in batching process. We evaluated the interference of time exposure parameters and the level of the liquid blades (15, 30 and 45 seconds of exposure for the liquid blades levels of 2 and 4 cm; 30, 60 and 90 seconds of exposure for the liquid blade level of 6 cm). We conducted a set of three tests for each liquid blade level applied. The tests were named ALL2, ALL4 and ALL6 in the levels of 2, 4 and 6 respectively. The efficiency was checked using the indicating microorganisms Clostridium perfringens (C. perfingens), coliphages, Total Coliforms (TC) and Escherichia coli (E. coli). After the disinfection by the UV radiation were carried out some tests to evaluate the possibility of microbiologic recovering (photoreactivation and dark repair) of indicating microorganisms E. coli and TC. The parameters physical-chemical turbidity, absorbance in 254 nm and total suspended solids (TSS) has influenced the microbial inactivation by UV radiation. There was a great plunge of the indicating microorganisms E. coli, TC (except for test ALL4) and coliphages proved trough the analyses of repeated measures variance with a significant level of 5%. C. perfringens was the indicating microorganism that showed the high resistance against the UV radiation in all of the tests. The test ALL2 was the one that showed the best results, after 30 seconds of exposure (effective average dose of 68,04 mWs/cm²) there was inactivation of approximately 1,65 ± 0,29 log for coliphages; 2,30 ± 1,55 log for E. coli and 3,85 ± 2,17 for TC. Keeping the exposure time of 30 seconds and varying the level of the liquid blade, the efficiencies of inactivation showed decreasing results comparing to the test ALL2. Although, in the tests of microbiologic recovering, the photoradiation was more perceptible than the dark repair; therefore, both repairing mechanisms were less significant.